Methodological foundations of educational research activities of Orthodox Brotherhoods in Western Ukraine in the interwar period of 1921-1939 years. (Pedagogy of Higher and Secondary Education, 2012)
Mishkareva S. Methodological foundations of educational research activities of Orthodox Brotherhoods in Western Ukraine in the interwar period of 1921-1939 years.The analysis of methodological basis and main theoretical approaches to the issue of educational activity researching of orthodox brotherhoods in Western Ukraine during the interwar period of 1921-1939 which are used in history of education as necessary ores for holistic and systemic analysis of historical and pedagogical phenomena and processes is done in the article.
Keywords: orthodox brotherhoods; methodology of research; educative activity; theoretical analysis